Pengaruh Kepemimpinan Etis terhadap Kinerja Pegawai Negeri Sipil - Zahrotul Lailatal Maghfiroh; Agil Bisifa (Perspektif Administrasi Publik dan hukum, 2025)
This study aims to understand the influence of ethical leadership on the performance of Civil Servants (PNS) in government organizations. Ethical leadership is considered important to create a conducive work environment, increase job satisfaction, productivity, and efficiency. The method used is a literature study, which examines various previous research sources to identify the influence of ethical leadership on PNS performance and factors that can strengthen or weaken the relationship. The results of the study indicate that ethical leadership has a positive effect on PNS performance through increased motivation, commitment, and job satisfaction. This finding also shows that the influence of ethical leadership can be strengthened by an organizational culture that supports ethical values and a fair reward system. The implications of this study indicate that strengthening ethical leadership needs to be accompanied by character development policies and training for leaders and employees in order to create an effective and accountable work environment. Overall, this study supports the application of ethical leadership as a strategy to improve performance in the public sector and improve the quality of public services.